2006
DOI: 10.1073/pnas.0602025103
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for metabolic and reproductive phenotypes in mothers of women with polycystic ovary syndrome

Abstract: Dyslipidemia is a feature of polycystic ovary syndrome (PCOS), but its pathogenesis remains controversial. We performed this study of mothers of women with PCOS to test the hypothesis that dyslipidemia is a heritable trait in families of women with PCOS and to investigate the impact of age on reproductive and metabolic phenotypes. Fasting blood was obtained in 215 non-Hispanic white mothers of women with PCOS and 62 control women. The prevalence of metabolic syndrome was compared with that in nonHispanic white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 49 publications
5
53
0
4
Order By: Relevance
“…In addition, the prevalence of metabolic syndrome is increased in these groups (3,9). Further, increased LDL levels and metabolic syndrome are significantly associated with hyperandrogenemia, suggesting that the cardinal reproductive feature of the syndrome plays a direct role in the etiology of the associated metabolic abnormalities (3,9). Consistent with this hypothesis, the PCOS susceptibility allele is associated with markers of insulin resistance in women with PCOS (5).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…In addition, the prevalence of metabolic syndrome is increased in these groups (3,9). Further, increased LDL levels and metabolic syndrome are significantly associated with hyperandrogenemia, suggesting that the cardinal reproductive feature of the syndrome plays a direct role in the etiology of the associated metabolic abnormalities (3,9). Consistent with this hypothesis, the PCOS susceptibility allele is associated with markers of insulin resistance in women with PCOS (5).…”
supporting
confidence: 72%
“…Elevated LDL cholesterol levels are the most consistent lipid abnormality in affected women as well as in their sisters and mothers (3,8 -10). In addition, the prevalence of metabolic syndrome is increased in these groups (3,9). Further, increased LDL levels and metabolic syndrome are significantly associated with hyperandrogenemia, suggesting that the cardinal reproductive feature of the syndrome plays a direct role in the etiology of the associated metabolic abnormalities (3,9).…”
mentioning
confidence: 88%
“…Our studies indicate that mothers and brothers also have elevated LDL levels and evidence for insulin resistance [102]. Therefore, reproductive and metabolic abnormalities track together in PCOS families suggesting that they may reflect variation in the same gene or in closely linked genes, be causally related, or have a common pathogenesis.…”
Section: Evidence For a Genetic Susceptibility To Pcosmentioning
confidence: 88%
“…Moini et al [25] reported a significantly increased prevalence of maternal DM in the PCOS group than the control group, and a maternal history of DM was more predictive than a paternal history of DM. Moreover, mothers of women with PCOS had a higher HOMA-IR, an increased prevalence of MetS, and an elevated risk for CHD [26]. Whether paternal or maternal inheritance underlies PCOS has been a matter of controversy and varies in different populations and races.…”
Section: Discussionmentioning
confidence: 99%